1991
DOI: 10.1042/bj2800427
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and secretion of a cobalamin-binding protein by HT 29 cell line

Abstract: An HT 29 cell line derived from human colonic carcinoma was shown to synthesize and release a cobalamin-binding protein. The cobalamin-binding protein was classified as transcobalamin (TC). By gel filtration on Sephacryl S200 HR, we observed that the secreted protein bound to cobalamin had the same size as plasma transcobalamin. Like transcobalamin, the cobalamin-binding protein bound cobalamin but not cobinamide. Purification of the cobalamin-binding protein was performed by heparin-Sepharose affinity chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…2). We have also observed such an increase, after the same culture time, for the synthesis of transcobalamin II by HT 29 cells [4]. This delay corresponded to the time needed by the cells to reach eonfluency [6].…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…2). We have also observed such an increase, after the same culture time, for the synthesis of transcobalamin II by HT 29 cells [4]. This delay corresponded to the time needed by the cells to reach eonfluency [6].…”
Section: Resultsmentioning
confidence: 50%
“…The receptor is located only in the distal ileum of adult humans, but it is also detected in the jejunum and in the colon of fetus, before 25 weeks of gestational age [2,3]. Recently, we have reported the synthesis of transcobalamin II and of a receptor for IF-Cbl in HT 29 cells [4,5]. HT 29 is a cell line, derived from a human colon carcinoma, which shares the same brush border enzymes than fetal cells and grows as polarized monolayers in culture [6].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Ramanujam and coworkers observed that Caco-2 cells only secrete TcII into the basal medium of transwell cultures with no apparent secretion of VB 1 2 -binders into the apical medium (Ramanujam et al, 1991b). In contrast, Hc was found to be secreted into the cell medium of HT-29 cell cultures (Schohn et al, 1991).…”
Section: Cell Models Of Vitamin B 12 Transportmentioning
confidence: 86%
“…Secretion (at least from fibroblasts) is blocked by cycloheximide and puromycin (Green et al, 1976). A TCII-like molecule is synthesized and secreted from HT 29 cells and Caco-2 cells (Schohn et al, 1991;Dix et al, 1990). The protein has a molecular weight of 44 kDa with an isoelectric point of 6.4, and is immunologically cross-reactive with human TCII (Tables I and II) (Schohn et al, 1991).…”
Section: Synthesis and Secretionmentioning
confidence: 99%
See 1 more Smart Citation